Fatal Granulomatous Amoebic Encephalitis Caused by Acanthamoeba in a Patient With Kidney Transplant: A Case Report. (10th July 2015) - Salameh, Ahmad; Bello, Nancy; Becker, Jennifer; Zangeneh, Tirdad
Abstract: Granulomatous amoebic encephalitis (GAE) due to Acanthamoeba is almost a uniformly fatal infection in immune-compromised hosts despite multidrug combination therapy. We report a case of GAE in a female who received a deceased donor kidney graft. She was treated with a combination of miltefosine, pentamidine, sulfadiazine, fluconazole, flucytosine, and azithromycin.